Exploring potential glacial lakes using geo-spatial techniques in Eastern Hindu Kush Region, Pakistan - Mariam Sarwar; Shakeel Mahmood (Natural Hazards Research, 2024)
The study aimed to investigate the potential glacial lakes in response to climate change and the associated risk of glacial lake outburst floods (GLOFs). Remote sensing data and GIS techniques were utilized to analyze glacial lakes, employing empirical models to estimate their area, volume, and depth. The Normalized Difference Water Index (NDWI) was applied to detect changes in glacial lakes using Sentinel imagery. The findings revealed a notable increase in both the number and surface area of glacial lakes over the past two decades. Specifically, the number of glacial lakes rose from 101 in 2000 to 162 in 2020, while their combined surface area expanded from 9.72 km2 to 12.36 km2 during the same period. Among these lakes, 31 were identified as Potentially Dangerous Glacial Lakes (PDGLs), with 6 located in Chitral, 16 in Swat, and 9 in Upper Dir. Two lakes were classified as high potential glacial lakes, with depths estimated at 41.86 ​m and 30.43 ​m. Continued monitoring of these glacial lakes and their susceptibility to GLOFs is crucial in the face of ongoing climate change. Long-term planning and adaptation strategies are necessary to safeguard the well-being and safety of communities residing in these vulnerable regions. By understanding the evolving characteristics of these lakes, researchers and policymakers can better prepare for and mitigate the impacts of GLOFs on downstream communities and infrastructure.